TANGGUNG JAWAB PELAKU USAHA BERKAITAN DENGAN PENJUALAN BAHAN MAKANAN KADALUWARSA DAN TIDAK MEMENUHI STANDAR YANG DITENTUKAN (STUDI PUTUSAN PENGADILAN NEGERI JEMBER NOMOR 258/PID.SUS/2018/PN.JMR.) - Darren Marvel; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2020)
Currently there are still many packaged food products circulating on the market that do not meet the specified standards, namely not including expiration date, composition, net weight and name and address of producers, so this is endangering consumers. The problem faced in scientific writing is how the responsibilities of business actors with regard to the sale of expired foodstuffs and do not meet the specified standards (Study of the Jember District Court Decision Number 258 /Pid.Sus/2018/PN.Jmr.) The research method used in scientific writing is normative legal research. The results of the research show that the responsibility of the business actor in relation to the sale of expired foodstuffs does not meet the specified standards (Jember District Court Decision Study Number 258/Pid.Sus/2018/PN.Jmr.) Is that the business actor is responsible for his mistakes as regulated Article 8 paragraph (1) UUPK and Article 19 paragraph (1) UUPK state that: